Safety and outcome of coronary interventions with special reference to anticoagulation and stent type - Annala, Antti-Pekka (Turun yliopiston julkaisuja - Annales Universitatis Turkuensis, Sarja - ser. D osa - tom. 1191: Medica - Odontologica, 2015)
University of Turku, Faculty of Medicine, Department of Cardiology and Cardiovascular Medicine, Doctoral Programme of Clinical Investigation, Heart Center, Turku University Hospital, Turku, Finland Division of Internal Medicine, Department of Cardiology, Seinäjoki Central Hospital, Seinäjoki, Finland Heart Center, Satakunta Central Hospital, Pori, Finland Annales Universitatis Turkuensis Painosalama Oy, Turku, Finland 2015 Antithrombotic therapy during and after coronary procedures always entails the challenging establishment of a balance between bleeding and thrombotic complications. It has been generally recommended to patients on long-term warfarin therapy to discontinue warfarin a few days prior to elective coronary angiography or intervention to prevent bleeding complications. Bridging therapy with heparin is recommended for patients at an increased risk of thromboembolism who require the interruption of anticoagulation for elective surgery or an invasive procedure. In study I, consecutive patients on warfarin therapy referred for diagnostic coronary angiography were compared to control patients with a similar disease presentation without warfarin. The strategy of performing coronary angiography during uninterrupted therapeutic warfarin anticoagulation appeared to be a relatively safe alternative to bridging therapy, if the international normalized ratio level was not on a supratherapeutic level. In-stent restenosis remains an important reason for failure of long-term success after a percutaneous coronary intervention (PCI). Drug-eluting stents (DES) reduce the problem of restenosis inherent to bare metal stents (BMS). However, a longer delay in arterial healing may extend the risk of stent thrombosis (ST) far beyond 30 days after the DES implantation. Early discontinuation of antiplatelet therapy has been the most important predisposing factor for ST. In study II, patients on long-term oral anticoagulant (OAC) underwent DES or BMS stenting with a median of 3.5 years’follow-up. The selective use of DESs with a short triple therapy seemed to be safe in OAC patients, since late STs were rare even without long clopidogrel treatment. Major bleeding and cardiac events were common in this patient group irrespective of stent type. In order to help to predict the bleeding risk in patients on OAC, several different bleeding risk scorings have been developed. Risk scoring systems have also been used also in the setting of patients undergoing a PCI. In study III, the predictive value of an outpatient bleeding risk index (OBRI) to identify patients at high risk of bleeding was analysed. The bleeding risk seemed not to modify periprocedural or long-term treatment choices in patients on OAC after a percutaneous coronary intervention. Patients with a high OBRI often had major bleeding episodes, and the OBRI may be suitable for risk evaluation in this patient group. Optical coherence tomography (OCT) is a novel technology for imaging intravascular coronary arteries. OCT is a light-based imaging modality that enables a 12–18 µm tissue axial resolution to visualize plaques in the vessel, possible dissections and thrombi as well as, stent strut appositions and coverage, and to measure the vessel lumen and lesions. In study IV, 30 days after titanium-nitride-oxide (TITANOX)-coated stent implantation, the binary stent strut coverage was satisfactory and the prevalence of malapposed struts was low as evaluated by OCT. Long-term clinical events in patients treated with (TITANOX)-coated bio-active stents (BAS) and paclitaxel-eluting stents (PES) in routine clinical practice were examined in study V. At the 3-year follow-up, BAS resulted in better long-term outcome when compared with PES with an infrequent need for target vessel revascularization. Keywords: anticoagulation, restenosis, thrombosis, bleeding, optical coherence tomography, titanium

SEPELVALTIMOIDEN PALLOLAAJENNUSHOIDON TURVALLISUUS JA TULOKSET VERENOHENNUSHOIDON AIKANA JA ERI STENTTITYYPEILLÄ Sydänkeskus, Turun yliopistollinen keskussairaala, Kardiologia ja kardiovaskulaarilääketiede, Kliininen Tohtoriohjelma, Turun yliopisto Sisätautien yksikkö, Sydänosasto, Seinäjoen keskussairaala, Seinäjoki Sydänkeskus, Satakunnan keskussairaala, Pori Annales Universitatis Turkuensis Painosalama Oy, Turku, Finland 2015 Hyytymisenestolääkkeiden käyttö sepelvaltimotoimenpiteiden yhteydessä ja niiden jälkeen on haastavaa tasapainottelua vuotojen ja hyytymien aiheuttamien komplikaatioiden välillä. Aikaisemmin on suositeltu verenohennushoidon lopettamista muutama päivä ennen suunniteltua sepelvaltimotoimenpidettä. Potilailla, joilla on korkea tukosriski, on suositeltu hepariinin käyttöä ns. siltahoitona verenohennuslääkehoidon tauon aikana. Tutkimuksessa todettiin, että sepelvaltimoiden varjoainekuvaus voidaan tehdä varsin turvallisesti ilman hepariini siltahoitoa keskeytymättömän verenohennushoidon aikana, jos verenohennustaso on suositellulla hoitoalueella. Lääkeainestenteillä on pystytty vähentämään metallistenteille yleistä suonen uudelleenahtautumista sepelvaltimon pallolaajennuksella hoidetussa kohdassa. Lääkeaineen hidastaessa stentatun suonen alueen parantumista riski hyytymän kehittymiseen lääkeverkon sisälle on suurentunut, ja riski voi jatkua merkittävästi kauemmin kuin 30 vuorokautta. Tehokkaalla hyytymisenestolääkityksellä pyritään estämään stentinsisäisten hyytymien kehittyminen. Aikainen hyytymisenestolääkityksen lopettaminen on todettu tämän ongelman merkittävimmäksi riskitekijäksi. Tutkimuksessa osoitettiin verenohennuspotilailla 3,5 vuoden seurannassa vähän myöhäisiä stenttitrombeja, vaikka käytettiin lääkeainestenttejä ja lyhyttä klopidogreelihoitoa hyytymien estossa. Kuitenkin pallolaajennetuilla verenohennuspotilailla todettiin paljon verenvuoto – ja muita komplikaatioita. Lukuisia pisteytyksiä on kehitetty verenohennuspotilaan vuotoriskin arvioimiseksi. Samoja pisteytyksiä on käytetty myös pallolaajennuspotilaan vuotoriskin arviointiin. Tutkimuksessa tarkasteltiin outpatient bleeding risk index (OBRI) -pisteytyksen kykyä löytää korkean vuotoriskin pallolaajennuspotilaat. Korkeat OBRI-pisteet saaneilla potilailla esiintyi enemmän vuotoja, mikä viittaa OBRI-pisteytyksen käyttökelpoisuuteen tässä potilasjoukossa. Valokerroskuvaus on uusi tekniikka, jolla voidaan kuvata sepelvaltimoa suonen sisältä. Valokerroskuvauksella voidaan erottaa kudoksia 12–18 mikrometrin tarkkuudella. Sillä kuvautuvat hyvin suonen sisäpinnan plakit, mahdolliset seinämän repeämät ja hyytymät sekä stentin asettuminen suonen seinämää vasten ja stentin peittyminen suonen parantuessa. Myös suonen koon ja kohteiden tarkka mittaus on mahdollista. Titaani-typpioksidilla (TITANOX) päällystettyjen stenttien todettiin valokerroskuvauksella arvioituna pääsääntöisesti peittyneen kudoksella jo 30 vuorokauden kuluttua pallolaajennuksesta. Myös stentin asettuminen suonen seinämään oli hyvä. Tutkimuksessa todettiin kolmen vuoden seurannassa TITANOX-päällysteisellä stentillä hoidetuilla potilailla merkittävästi vähemmän sydänkomplikaatioita paklitakseli-päällysteisillä lääkestenteillä hoidettuihin potilaisiin verrattuna. Uusintatoimenpiteitä tarvittiin enemmän lääkestenteillä hoidetuilla potilailla. Avainsanat: antikoagulaatio, restenoosi, tromboosi, verenvuoto valokerroskuvaus, titaani